Measurement of the rapidity and transverse momentum distributions of Z bosons in pp collisions at √(s)=7TeV - Chatrchyan, S. (2012)
Measurements of the normalized rapidity (y) and transverse-momentum (q T) distributions of Drell-Yan muon and electron pairs in the Z-boson mass region (60<M<120GeV) are reported. The results are obtained using a data sample of proton-proton collisions at a center-of-mass energy of 7 TeV, collected by the CMS experiment at the Large Hadron Collider (LHC), corresponding to an integrated luminosity of 36pb -1. The distributions are measured over the ranges |y|<3.5 and q T< 600GeV and compared with quantum chromodynamics (QCD) calculations using recent parton distribution functions to model the momenta of the quarks and gluons in the protons. Overall agreement is observed between the models and data for the rapidity distribution, while no single model describes the Z transverse-momentum distribution over the full range. © 2012 CERN.